Core-shell structure high-nickel ternary precursor and preparation method thereof

By designing a high-nickel ternary precursor with a core-shell structure, combining the synthesis conditions of high pH value and ammonia concentration, the problem of degradation of cyclic stability of high-nickel ternary materials is solved, and excellent performance of high capacity and long cycles is achieved.

CN119660834AActive Publication Date: 2025-03-21JINCHUAN GRP NICKEL SALTS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411937991.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

While increasing the specific capacity, high-nickel ternary materials have significantly reduced cycle stability, thermal stability and safety performance, limiting their commercial applications.

Method used

A high-nickel ternary precursor is adopted for core-shell structure, which includes loose core, intermediate layer and dense shell. By controlling the pH value and ammonia concentration during the synthesis process, it ensures the increase in negative charge on the particle surface and the optimization of the crystal surface peak strength ratio, thereby improving the cyclic stability and capacity of the material.

Benefits of technology

It realizes high capacity and long cycle life of high nickel ternary cathode material, combines excellent cycle stability and high specific capacity, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660834A_ABST
    Figure CN119660834A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field, in particular to a high-nickel ternary precursor with a core-shell structure and a preparation method thereof, and the preparation method comprises the following steps: preparing an early-stage solution: preparing a Ni, Co and Mn metal mixed solution, a precipitator solution and a complexing agent solution; preparing a reaction kettle base solution; making an inner core: keeping the stirring of the reaction kettle to be started, continuously adding the metal mixed solution, a precipitant and a complexing agent into the base solution of the reaction kettle at different flow speeds, carrying out a co-precipitation reaction, sampling the fed solution per hour, and detecting the granularity of the slurry to obtain the inner core with the highest porosity; manufacturing a middle layer: obtaining the middle layer with the porosity lower than that of the inner core; making a shell; according to the invention, the precursor structure is designed to be a core-shell structure: a loose inner core-a middle layer-a compact shell, and a loose transition layer of about 2 [mu] m is arranged between the loose inner core and the compact shell, so that performance exertion between the inner core and the shell is effectively linked; the high-nickel ternary positive electrode material obtained after subsequent lithium mixing and sintering has excellent performance of high capacity and long cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a core-shell structured high-nickel ternary precursor and a preparation method thereof. Background Art

[0002] As the nickel content in the ternary material increases, its specific capacity gradually increases, but at the same time the material's cycle stability, thermal stability and safety performance are significantly reduced, which greatly limits the large-scale commercial application of ultra-high nickel ternary materials. How to ensure high capacity while having excellent cycle stability has always been the research focus of high-nickel ternary positive electrode materials. In order to solve the problem of decreased cycle stability caused by the increase in nickel content in ternary materials, the comprehensive performance of ternary materials is currently further improved by doping, coating and other means. Doping modification mainly replaces the positive electrode material with other atoms such as Mg, Mn, W, etc. to improve its structural stability. In addition, effective surface coating can reduce the reaction activity of the ternary material with the electrolyte, reduce the occurrence of side reactions, and thus improve the cycle stability of the material.

[0003] In general, the coating layer is usually an inert material that does not have electrochemical activity, such as Al2O3, ZrO2, LiF and TiO2. If the coating layer is too thick, it will affect the Li+ transport on the positive electrode surface, thereby limiting the material capacity and reducing its rate performance; if the coating layer is too thin, it cannot effectively improve the long-term cycle stability of the positive electrode, because the coating thin layer is easily dissolved and detached after being corroded by the electrolyte for a long time, and the positive electrode surface is still attacked by the electrolyte and its decomposition products, causing capacity decay. However, coating these "inactive" materials on lithiated layered transition metal oxides inevitably increases production costs. Therefore, a more cost-effective method is needed to improve the cycle life of nickel-rich materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a stable and high-performance core-shell structure high-nickel ternary precursor and a preparation method thereof.

[0005] To solve the above problems, one of the technical solutions of the present invention is achieved in the following way: a method for preparing a core-shell structure high-nickel ternary precursor comprises the following steps: S1, preparing the preliminary solution: preparing a mixed solution of Ni, Co, and Mn metals, a precipitant solution, and a complexing agent solution; preparing a reaction kettle bottom solution; S2, making the inner core: keep the stirring of the reactor on, continuously introduce nitrogen to ensure that the oxygen content of the reactor does not exceed 300ppm, the reaction temperature is 35~55℃, and the metal mixture, precipitant and complexing agent are continuously added to the bottom liquid of the reactor at different flow rates to carry out co-precipitation reaction. Sample the liquid every hour to detect the slurry particle size. The slurry particle size at 1h and 2h meets the following requirements: 4um<D50-1<4.5um, 3.5um<D50-2<4um, and the inner core with the highest looseness is obtained; S3, making the middle layer: after 2 hours of liquid feeding, adjust the flow rate of the metal liquid and the complexing agent in step S2, and the slurry particle size at 3 hours and 4 hours meets the following requirements: 4.8um<D50-3<5.2um, 5.5um<D50-4<6um, and obtain the middle layer with a looseness inferior to the inner core; S4, making the shell: after 4 hours of liquid feeding, the flow rates of the metal liquid and the complexing agent are restored to the same flow rates as in step S2, and the precipitant also adjusts the flow rate to ensure that the pH remains unchanged, and the reaction is continued until the slurry particle size in the reactor reaches 9-10 um, and the reaction is stopped to obtain a dense shell; S5, the coprecipitation product in step S4 is subjected to solid-liquid separation, washing, and drying to obtain a core-shell structure ternary precursor.

[0006] In the above step S1, the total molar concentration of the metal mixed solution is 1-2 mol / L; the precipitant solution is one or more of sodium hydroxide or potassium hydroxide, and its concentration is 6-10 mol / L; the complexing agent is ammonia water, and its concentration is 2-3 mol / L; the bottom liquid of the reactor is a mixture of pure water and complexing agent, and the precipitant is added to adjust the pH to 12.00-13.00, and the bottom liquid ammonia concentration is 0.7-1.5 mol / L.

[0007] In the above step S2, the metal liquid flow rate and the complexing agent flow rate are quantitatively controlled to V1 and V2 respectively. The complexing agent flow rate V2 is controlled so that the mother liquor ammonia concentration in the process is 0.8~1.2mol / L. The precipitant flow rate is automatically adjusted according to the pH value feedback result, and the process pH is 12.00~12.50.

[0008] In the above step S3, the flow rates of the molten metal and the complexing agent in step S2 are adjusted to V3 and V4 respectively, V3 / V1=V4 / V2 and the ratio range is between 4 and 6, and the precipitant adjusts the flow rate to ensure that the pH remains unchanged, and the pH is maintained at 12.00-12.50.

[0009] In the above step S4, the flow rates of the molten metal and the ammonia water are restored to V1 and V2, and the reaction is continued to the target particle size for 10 to 15 hours, and the solid content during the reaction is 1.15 to 1.25 g / mL.

[0010] The second technical solution of the present invention is achieved by the following method: a core-shell structure high nickel ternary precursor is obtained according to the preparation method of the core-shell structure high nickel ternary precursor, and the precursor chemical formula is Ni x Co y Mn z (OH)2, 0.8<x<1, 0<y<0.1, x+y+z=1, D509~10um, the peak intensity ratio of (001) crystal plane to (101) crystal plane 1<I(001) / I(101)<1.2.

[0011] The above-mentioned precursor is a core-shell structure, including a loose core, an intermediate layer and a dense outer shell, wherein the loose core has a size of 3.5~4um, the intermediate layer has a size of 1.5~2.5um, and the dense outer shell has a size of 3.5~4.5um.

[0012] The third technical solution of the present invention is achieved in the following way: a high-nickel ternary positive electrode material, which is formed by mixing a core-shell structure high-nickel ternary precursor with a lithium source and then sintering at high temperature.

[0013] The precursor structure design of the present invention is a core-shell structure: loose inner core-middle layer-dense outer shell, the loose inner core size is 3.5~4um, the middle layer size is 1.5~2.5um, the dense outer shell size is 3.5~4.5um, and there is a loose transition layer of about 2um between the loose inner core and the dense outer shell, which effectively connects the performance between the inner core and the outer shell. After subsequent mixed lithium sintering, the high-nickel ternary positive electrode material has the excellent performance of high capacity and long cycle.

[0014] The present invention maintains a high pH value during the synthesis process so that a large amount of OH- is distributed on the surface of the particles. The increase in surface negative charge can increase the exposure of the (001) crystal plane and improve the peak intensity ratio of the (001) and (101) diffraction peaks. The designed peak intensity ratio of the (001) crystal plane to the (101) crystal plane is between 1<I(001) / I(101)<1.2. After subsequent mixed lithium sintering, a high-nickel ternary positive electrode material is obtained, which has excellent capacity and cycle performance.

[0015] The ternary precursor synthesis process of the present invention continuously maintains a pH value above 12.00. Matching a high ammonia ratio under high OH- concentration can well control the supersaturation of the system. The mother liquor ammonia concentration is controlled at 0.8-1.2 mol / L during the synthesis process. If the ammonia concentration is lower than this range, the complexing effect is poor, resulting in the particle size in the process stage failing to meet the requirements. If the concentration is higher than this range, the complexing effect will reach a maximum value, resulting in a waste of raw materials.

[0016] The invention has simple process control, convenient production operation and can realize large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0018] Figure 1 This is the SEM image of the core-shell structured high-nickel ternary precursor prepared in Example 4.

[0019] Figure 2 This is an internal cross-sectional view of the core-shell structured high-nickel ternary precursor prepared in Example 4.

[0020] Figure 3 This is the SEM diffraction pattern of the core-shell structured high-nickel ternary precursor prepared in Example 5.

[0021] Figure 4 This is an internal cross-sectional view of the core-shell structured high-nickel ternary precursor prepared in Example 5. DETAILED DESCRIPTION

[0022] The present invention is not limited by the following embodiments, and specific implementation methods can be determined based on the technical solution of the present invention and actual conditions.

[0023] Embodiment 1: The embodiment of the present invention discloses a method for preparing a core-shell structure high nickel ternary precursor, comprising the following steps: S1, preparing the preliminary solution: preparing a mixed solution of Ni, Co, and Mn metals, a precipitant solution, and a complexing agent solution; preparing a reaction kettle bottom solution; S2, making the inner core: keep the stirring of the reactor on, continuously introduce nitrogen to ensure that the oxygen content of the reactor does not exceed 300ppm, the reaction temperature is 35~55℃, and the metal mixture, precipitant and complexing agent are continuously added to the bottom liquid of the reactor at different flow rates to carry out co-precipitation reaction. Sample the liquid every hour to detect the slurry particle size. The slurry particle size at 1h and 2h meets the following requirements: 4um<D50-1<4.5um, 3.5um<D50-2<4um, and the inner core with the highest looseness is obtained; S3, making the middle layer: after 2 hours of liquid feeding, adjust the flow rate of the metal liquid and the complexing agent in step S2, and the slurry particle size at 3 hours and 4 hours meets the following requirements: 4.8um<D50-3<5.2um, 5.5um<D50-4<6um, and obtain the middle layer with a looseness inferior to the inner core; S4, making the shell: after 4 hours of liquid feeding, the flow rates of the metal liquid and the complexing agent are restored to the same flow rates as in step S2, and the precipitant also adjusts the flow rate to ensure that the pH remains unchanged, and the reaction is continued until the slurry particle size in the reactor reaches 9-10 um, and the reaction is stopped to obtain a dense shell; S5, the coprecipitation product in step S4 is subjected to solid-liquid separation, washing, and drying to obtain a core-shell structure ternary precursor.

[0024] Wherein, in step S1, the total molar concentration of the metal mixed solution is 1-2 mol / L; the precipitant solution is one or more of sodium hydroxide or potassium hydroxide, and its concentration is 6-10 mol / L; the complexing agent is ammonia water, and its concentration is 2-3 mol / L; the bottom liquid of the reactor is a mixture of pure water and complexing agent, and the precipitant is added to adjust the pH to 12.00-13.00, and the bottom liquid ammonia concentration is 0.7-1.5 mol / L.

[0025] Among them, in step S2, the metal liquid flow rate and the complexing agent flow rate are quantitatively controlled to V1 and V2 respectively, and the complexing agent flow rate V2 is controlled so that the mother liquor ammonia concentration in the process is 0.8~1.2mol / L, and the precipitant flow rate is automatically adjusted according to the pH value feedback result, and the process pH is 12.00~12.50.

[0026] Among them, in step S3, the flow rates of the metal liquid and the complexing agent in step S2 are adjusted to V3 and V4 respectively, V3 / V1=V4 / V2 and the ratio range is between 4 and 6, and the precipitant adjusts the flow rate to ensure that the pH remains unchanged, and the pH is maintained at 12.00~12.50.

[0027] Among them, in step S4, the flow rates of the molten metal and ammonia water are restored to V1 and V2, and the reaction is continued to the target particle size for 10-15 hours, and the solid content of the reaction process is 1.15-1.25 g / mL.

[0028] In the embodiment of the present invention, the bottom liquid of the reactor is pure water at the initial stage of the ternary precursor liquid injection, the system has a high supersaturation, the nucleation rate is dominant, and the particle size will gradually decrease with the reaction time after the liquid is injected. The present invention strictly controls the nucleation time and the corresponding nucleation particle size. These two dimensions determine the number of crystal nuclei. The nucleation time is 2h, and the nucleation particle size is 3.5um<D50-2 <4um. To meet the initial nucleation number, the particle size of 1h needs to meet 4um<D50-1 <4.5um. If it is lower than this range, the particle size of 2h will be lower than 3.5um, and the number of nucleations is too much. If it is higher than this range, the particle size of 2h will be higher than 4.5um, and the number of nucleations is too small. The core with the highest porosity is obtained at this stage.

[0029] In addition, by controlling the number of crystal nuclei and entering the crystal growth stage, the metal liquid flow rate is greatly increased by multiples. On the one hand, due to the instantaneous generation of a large amount of solute under the high metal liquid flow rate, the primary particle refinement can be effectively achieved. On the other hand, the crystal growth rate is positively correlated with the increase in the metal liquid flow rate, which increases the crystal growth rate by 4 to 6 times. The particle size suddenly changes at 3 hours, with an increase of 1 to 1.5 um. The particle size increase at 4 hours is between 0.7 and 1 um, further forming a 2 um loose layer, whose porosity is inferior to the loose inner core.

[0030] Finally, after the particle size mutation ends, the metal liquid flow rate is restored to the original flow rate to achieve slow growth and obtain a dense shell.

[0031] In summary, the present invention maintains a high pH during the synthesis process so that a large amount of OH- is distributed on the surface of the particles. The increase in surface negative charge can increase the exposure of the (001) crystal plane and improve the peak intensity ratio of the (001) and (101) diffraction peaks. The designed peak intensity ratio of the (001) crystal plane to the (101) crystal plane is between 1<I(001) / I(101)<1.2. After subsequent mixed lithium sintering, a high-nickel ternary positive electrode material is obtained, which has excellent capacity and cycle performance.

[0032] At the same time, the ternary precursor synthesis process of the present invention continuously maintains a pH value above 12.00, and matching a high ammonia ratio under high OH- concentration can well control the supersaturation of the system. The mother liquor ammonia concentration is controlled at 0.8-1.2 mol / L during the synthesis process. The ammonia concentration is lower than this range and the complexing effect is poor, resulting in the particle size in the process stage failing to meet the requirements. The complexing effect will reach a maximum value above this range, resulting in a waste of raw materials. The process control of the present invention is simple, the production operation is convenient, and large-scale preparation can be achieved.

[0033] Example 2: The present invention discloses a core-shell structure high nickel ternary precursor, which is obtained according to the preparation method of the core-shell structure high nickel ternary precursor, and the precursor chemical formula is Ni x Co y Mn z (OH)2, 0.8<x<1, 0<y<0.1, x+y+z=1, D509~10um, the peak intensity ratio of (001) crystal plane to (101) crystal plane 1<I(001) / I(101)<1.2.

[0034] Among them, the precursor is a core-shell structure, including a loose core, an intermediate layer and a dense outer shell, wherein the loose core has a size of 3.5~4um, the intermediate layer has a size of 1.5~2.5um, and the dense outer shell has a size of 3.5~4.5um.

[0035] In the embodiment of the present invention, the precursor structure is designed to be a core-shell structure: loose inner core-middle layer-dense outer shell, the loose inner core size is 3.5~4um, the middle layer size is 1.5~2.5um, and the dense outer shell size is 3.5~4.5um. There is a loose transition layer of about 2um between the loose inner core and the dense outer shell, which effectively connects the performance between the inner core and the outer shell. After subsequent mixed lithium sintering, the high-nickel ternary positive electrode material has the excellent performance of high capacity and long cycle.

[0036] Example 3: The embodiment of the present invention discloses a high-nickel ternary positive electrode material, which is formed by mixing a core-shell structure high-nickel ternary precursor with a lithium source and then sintering at high temperature.

[0037] Example 4: The present invention discloses a method for preparing a core-shell structured high-nickel ternary precursor, comprising the following steps: Step 1: prepare a mixed solution of Ni, Co and Mn metals, an 8 mol / L sodium hydroxide solution and a 2 mol / L ammonia solution, wherein the element ratio of Ni, Co and Mn is 94:05:01, and the total molar concentration of Ni, Co and Mn is 2.5 mol / L; Step 2, prepare the reaction base liquid: first add 150L of cold pure water into a 300L reactor, heat the reactor to 45°C, add ammonia solution and sodium hydroxide solution, keep the ammonia concentration of the reaction base liquid mother liquor at 1mol / L, pH 12.40-12.60, keep the reactor airtight, and continuously introduce nitrogen at a nitrogen flow rate of 0.3L / min; Step 3, start the reactor to stir, the stirring speed is 400rpm, the metal liquid and ammonia water are added to the reactor at 300ml / min and 250ml / min respectively through their respective corresponding pipes for 2h, the temperature in the reactor is 45°C, the pH is controlled at 12.20-12.40, and the slurry particle size in the reactor is monitored by sampling every hour. The D50 of the slurry in 1h is 4.2um, and the D50 of the slurry in 2h is 3.65um; Step 4: After the liquid is added for 2 hours, the flow rate distribution of the molten metal and ammonia water is adjusted to 1500ml / min and 1000ml / min, and the slurry particle size in the reactor is monitored every hour. The D50 of the slurry after 3 hours is 4.95um, and the D50 of the slurry after 4 hours is 5.68um. The pH is maintained at 12.20-12.40. Step 5: After the liquid is added for 4 hours, the flow rates of the metal liquid and ammonia water are restored to 300 ml / min and 250 ml / min respectively, and the pH is still maintained at 12.20-12.40. The reaction is continued for 13 times and the particle size is 9.7 um to end the reaction; Step 6: The coprecipitated product in step 5 is subjected to solid-liquid separation, washing, and drying to obtain a core-shell structure ternary precursor. The precursor obtained after washing and drying, the relevant data table is shown in Table 1.

[0038] Example 5: The difference from Example 4 is that in step 3, the pH value of the reaction liquid is 11.40-11.60, the ammonia concentration of the reactor mother liquid is 0.5 mol / L, and the synthesis process in subsequent steps 3, 4, and 5 maintains the reaction pH at 11.40-11.60, and the ammonia concentration of the reactor mother liquid is 0.5 mol / L. The precursor obtained after washing and drying, the relevant data table is shown in Table 1.

[0039] It can be seen from the data in Table 1 that the sample prepared in Example 5 has low tap density and large specific gravity, I(001) / (101)<1, and the electrical performance of the positive electrode material after mixed lithium sintering is slightly higher than that of the embodiment, and the capacity difference is within 1 mAh / g. However, the room temperature and high temperature cycle performance of Example 5 is seriously poor. The electrical performance of the positive electrode material after mixed lithium sintering of the precursor prepared in Example 4 has excellent cycle performance, taking into account the advantages of high capacity and long cycle.

[0040] From the comparison cross-section ( Figure 2 and Figure 4 ), Example 4 and Example 5 have loose cores, but Example 4 is designed with a loose core and a dense shell, and the shell of Example 5 continues the looseness of the core, Figure 1 and Figure 3 It can be seen from the SEM that the shell morphology of Example 4 is dense, and the surface of the high-nickel ternary precursor prepared by the core-shell structure design of the present invention has excellent performance in capacity and cycle.

Claims

1. A method for preparing a core-shell structured high-nickel ternary precursor, characterized in that: The following steps are involved: S1, preparing preliminary solution: preparing Ni, Co, Mn metal mixed solution, precipitant solution and complexing agent solution; preparing reaction kettle bottom solution; S2, making the inner core: keep the stirring of the reactor on, continuously introduce nitrogen to ensure that the oxygen content of the reactor does not exceed 300ppm, the reaction temperature is 35~55℃, and the metal mixture, precipitant and complexing agent are continuously added to the bottom liquid of the reactor at different flow rates to carry out co-precipitation reaction. Sample the liquid every hour to detect the slurry particle size. The slurry particle size at 1h and 2h meets the following requirements: 4um<D50-1<4.5um, 3.5um<D50-2<4um, and the inner core with the highest looseness is obtained; S3, making the middle layer: after 2 hours of liquid feeding, adjust the flow rate of the metal liquid and the complexing agent in step S2, and the slurry particle size at 3 hours and 4 hours meets the following requirements: 4.8um<D50-3<5.2um, 5.5um<D50-4<6um, and obtain the middle layer with a looseness inferior to the inner core; S4, making the shell: after 4 hours of liquid feeding, the flow rates of the metal liquid and the complexing agent are restored to the same flow rates as in step S2, and the precipitant also adjusts the flow rate to ensure that the pH remains unchanged, and the reaction is continued until the slurry particle size in the reactor reaches 9-10 um, and the reaction is stopped to obtain a dense shell; S5, the coprecipitation product in step S4 is subjected to solid-liquid separation, washing, and drying to obtain a core-shell structure ternary precursor.

2. The method for preparing a core-shell structured high-nickel ternary precursor according to claim 1, characterized in that: In the step S1, the total molar concentration of the metal mixed solution is 1-2 mol / L; the precipitant solution is one or more of sodium hydroxide or potassium hydroxide, and the concentration thereof is 6-10 mol / L; the complexing agent is ammonia water, and the concentration thereof is 2-3 mol / L; the bottom liquid of the reactor is a mixture of pure water and complexing agent, and the precipitant is added to adjust the pH to 12.00-13.00, and the bottom liquid ammonia concentration is 0.7-1.5 mol / L.

3. The method for preparing a core-shell structured high-nickel ternary precursor according to claim 1, characterized in that: In step S2, the metal liquid flow rate and the complexing agent flow rate are quantitatively controlled to V1 and V2 respectively, and the complexing agent flow rate V2 is controlled so that the mother liquor ammonia concentration in the process is 0.8-1.2 mol / L, and the precipitant flow rate is automatically adjusted according to the pH value feedback result, and the process pH is 12.00-12.

50.

4. The method for preparing a core-shell structured high-nickel ternary precursor according to claim 3, characterized in that: In step S3, the flow rates of the molten metal and the complexing agent in step S2 are adjusted to V3 and V4 respectively, V3 / V1=V4 / V2 and the ratio range is between 4 and 6, and the precipitant adjusts the flow rate to ensure that the pH remains unchanged, and the pH is maintained at 12.00-12.

50.

5. The method for preparing a core-shell structured high-nickel ternary precursor according to claim 4, characterized in that: In step S4, the flow rates of the molten metal and aqueous ammonia are restored to V1 and V2, and the reaction is continued to reach the target particle size for 10 to 15 hours, and the solid content during the reaction is 1.15 to 1.25 g / mL.

6. A core-shell structure high nickel ternary precursor, characterized in that: The method for preparing a core-shell structure high-nickel ternary precursor according to any one of claims 1 to 5 is obtained, wherein the precursor chemical formula is Ni x Co y Mn z (OH)2, 0.8<x<1, 0<y<0.1, x+y+z=1, D509~10um, the peak intensity ratio of (001) crystal plane to (101) crystal plane 1<I(001) / I(101)<1.

2.

7. The core-shell structure high nickel ternary precursor according to claim 6, characterized in that: The precursor is a core-shell structure, including a loose core, an intermediate layer and a dense outer shell, wherein the loose core has a size of 3.5-4 um, the intermediate layer has a size of 1.5-2.5 um, and the dense outer shell has a size of 3.5-4.5 um.

8. A high-nickel ternary positive electrode material, characterized in that: The material is formed by mixing the core-shell structure high-nickel ternary precursor described in any one of claims 6 to 7 with a lithium source and then sintering at high temperature.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material precursor and crystal face controllable growth method thereof, ternary positive electrode material and lithium ion battery

    CN112151790A

  • Ternary positive electrode material precursor and preparation method thereof, ternary positive electrode material, lithium ion battery, positive electrode and electric equipment

    CN114744164A

  • High-performance high-nickel low-cobalt ternary precursor and preparation method thereof

    CN118637680A

  • High-nickel positive electrode material and preparation method therefor

    WO2022268022A1